Principal leadership and school performance: Intergrating instructional and transformational leadership in South African schools context - George Nervious Shava (Association for Scientific Computing Electrical and Engineering(ASCEE), 2021)
This study aimed to examine the integration of instructional and transformational models of leadership in sustaining school improvement. The question of how the integration of instructional and transformational leadership in schools can influence learners' performance has received a significant amount of interest among researchers. Literature reviews have found two key approaches: educational and transformational leadership models to establish the most appropriate school leadership model. Therefore, this article reports on qualitative research used to arrive at an in-depth understanding of integrating instructional and transformational leadership in enhancing school performance. Data was collected through semi-structured interviews with principals in one educational province. Purposive sampling techniques were used to select participants for the study. Findings from the study established that integrating the two models had the potential to enhance learner performance. This study has shown that the integration of instructional and transformational leadership models led to a climate that promotes a culture of teaching and learning, hence increasing quality learning outcomes.